2022
DOI: 10.1177/21582440221113829
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management Practices and Inter-Organizational Project Performance: Moderating Effects of Inter-Organizational Communication, Relationship, and Process Conflicts in Healthcare

Abstract: The purpose of this study is to empirically examine the relationship between quality management practices (QMP) and inter-organizational project performance (IPP), as well as the moderating effects of inter-organizational communication (ICOM), relationship, and process conflicts in Pakistan’s-government healthcare organizations (NGOs) and public healthcare organizations. We developed a hypothetical model based on contingency theory. Using a self-administered questionnaire, the empirical data was collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…A convenient sampling technique is used to collect data from respondents. Few of the researchers confirmed that convenient sampling is an appropriate technique when researchers have limited time (Shah et al ., 2022), a budget (Sun et al ., 2022) and a large population (Rehman et al ., 2021). Moreover, researchers recognized that convenience sampling is a more suitable technique when researchers do not have a sampling frame (Sekaran and Bougie, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…A convenient sampling technique is used to collect data from respondents. Few of the researchers confirmed that convenient sampling is an appropriate technique when researchers have limited time (Shah et al ., 2022), a budget (Sun et al ., 2022) and a large population (Rehman et al ., 2021). Moreover, researchers recognized that convenience sampling is a more suitable technique when researchers do not have a sampling frame (Sekaran and Bougie, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…This study used partial least squares structural equation modeling (PLS-SEM) for data analysis, as recommended by previous researchers (Hair et al, 2020;Zeng et al, 2021). This technique is used for multivariate analysis because it can estimate theoretically established models of cause-effect relationships (Shah et al, 2022). This study used SmartPLS version 4 to test the measurement and structural models (Hair et al, 2017;Sarstedt and Cheah, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the researchers followed a convenience sampling technique to collect data. Prior researchers recognized that the convenience sampling technique is suitable when researchers have budget constraints (Sun et al ., 2022), time constraints (Shah et al. , 2022) and a large population (Rehman et al.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, the researchers followed a convenience sampling technique to collect data. Prior researchers recognized that the convenience sampling technique is suitable when researchers have budget constraints (Sun et al, 2022), time constraints (Shah et al, 2022) and a large population (Rehman et al, 2022a). Besides, the literature stated that convenience sampling is appropriate when research has issues with the sampling frame (Sekaran and Bougie, 2016).…”
Section: Population and Samplingmentioning
confidence: 99%